2011
DOI: 10.1080/13691058.2011.565369
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Latino men in rural communities in the Northwest: social environment and HIV/STI risk

Abstract: This study explored how migration-related socio-cultural and environmental factors interact to render immigrant Latino men residing in rural Oregon at increased risk for HIV/STI. More specifically, the paper describes the socio-demographic characteristics and sexual risk profile of immigrant Latino men and characterises the physical and socio-cultural contexts in which they reside. In-depth interviews were conducted with 49 men who newly immigrated to the USA and had recently engaged in sexual intercourse with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…People talk about ‘food deserts’ as a neighbourhood-level factor in obesity; I am making a parallel argument about ‘recreation-deserts’ as an influence on sexual risk practices. Substantial evidence suggests widespread sexual risk practices among these men (Parrado, Flippen, and McQuiston 2004; C Magis-Rodriguez et al 2009; Parrado and Flippen 2010b; Winett et al 2011). This does not mean that they are more sexually active than other groups, only that migrant men do, not surprisingly, have sex while they are in the USA, and that, like most other people, they do not always use condoms.…”
Section: Multi-sectoral Policies As Influences On Sexualitymentioning
confidence: 99%
“…People talk about ‘food deserts’ as a neighbourhood-level factor in obesity; I am making a parallel argument about ‘recreation-deserts’ as an influence on sexual risk practices. Substantial evidence suggests widespread sexual risk practices among these men (Parrado, Flippen, and McQuiston 2004; C Magis-Rodriguez et al 2009; Parrado and Flippen 2010b; Winett et al 2011). This does not mean that they are more sexually active than other groups, only that migrant men do, not surprisingly, have sex while they are in the USA, and that, like most other people, they do not always use condoms.…”
Section: Multi-sectoral Policies As Influences On Sexualitymentioning
confidence: 99%
“…As the economy soured, experiences of discrimination and social isolation became more salient and respondents who identified as crack-users reported crack binges and sustained use as a consequence. Similarly, immigrant Latino men in rural areas (e.g., farmworkers) or in urban settings other than day labourer sites have directly attributed their sexual risk-taking behaviours to feelings of loneliness and powerlessness in unfamiliar and inhospitable environments (Rhodes et al 2009; Winett et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Two qualitative studies were conducted with samples of immigrant heterosexual Hispanic men. Winnett and colleagues (2011) interviewed 49 of these men, and noted that participants reported that unstable employment and housing, decreased social support, loneliness, and a desire for sexual experimentation were related to inconsistent condom use with non-primary partners. Among men who engaged in high risk sex (i.e., sex without condoms), sexual behaviors was related to a lack of access to healthcare, multiple sexual partners, and sex with commercial sex workers (Apostolopoulos et al, 2006).…”
mentioning
confidence: 99%